PRODUCTION, PROCESSING, OPTIMIZATION, ORGANIZATION AND IMPROVEMENT OF AGRICULTURAL PRODUCTS IN OUR COUNTRY - Ziyodullayev Ilkhom Narkobilovich (European Science Publishing, 2025)
This is article reflects the importance of organizing clusters of agricultural production and processing in providing employment to the rural population, offers training based on the public-private partnership, as well as the direction of creating new jobs in clusters of agricultural production and processing.
Keywords: Providing employment to the population, public-private partnership, production and processing clusters of agricultural products, personnel training, creation of new jobs.